Optimized Dispatch of Park Integrated Energy System with Thermoelectric Flexible Response under Green Certificate-Carbon Trading Mechanism - Xinglong CHEN; Ximin CAO; Jie CHEN; Jun LIU; Yuchao ZHANG; Hongyin BAO (Zhongguo dianli)
In order to further improve the consumption rate of renewable energy and the low carbon and economy of the park integrated energy system (PIES), this paper proposes a low-carbon economic scheduling strategy for PIES, which considers the green certificate-carbon trading mechanism and the thermoelectric flexible response of combined heat and power (CHP) units. Firstly, a green certificate-carbon trading mechanism is established using the green certificate trading model and the stepped carbon trading model to improve the consumption of renewable energy within the system and decrease carbon emissions. Secondly, a thermoelectric flexible response model for CHP units is established by introducing the organic Rankine cycle into the system in combination with the conventional CHP units and electric boilers, thereby optimizing the system operations and providing greater application scope for the green certificate-carbon trading mechanism. Finally, with the goal of minimizing the total cost of the system, an optimization model of the PIES is constructed with consideration of the green certificate-carbon trading mechanism and the thermoelectric flexible response of the CHP units. The results show that the proposed strategy can improve the consumption rate of renewable energy, and reduce the carbon emissions and the total cost of the system.